Inhibiting amylolytic enzymes by both acarbose and cellobiose as a prelude to treating type II diabetes mellitus - Malgas, Malgas (University of Pretoria, 2024)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2024.